Effectiveness of Ultrasound To Reduce Pain In Low Back Pain : Literature Review - Zuyyinah Khairawati, Baiq; Putri Ramadhani, Okta; Nur Alpiah, Dini (International Journal of Social Research, 2024)
Low back pain (LBP) is a prevalent condition affecting a significant portion of the global population, often leading to reduced productivity and quality of life. It is broadly categorized into specific LBP, caused by identifiable pathophysiological mechanisms, and non-specific LBP, which lacks a clear origin and accounts for about 90% of cases. This study aims to evaluate the effectiveness of ultrasound therapy in reducing pain and improving functional status among patients with non-specific LBP. A literature review was conducted, analyzing studies from 2013 to 2023 that applied ultrasound therapy to LBP patients. The primary outcomes were pain reduction and functional improvement, measured using the Modified Oswestry Disability Index (MODI) and Visual Analogue Scale (VAS). The findings suggest that ultrasound therapy effectively alleviates pain and enhances functional status in LBP patients. The thermal and mechanical effects of ultrasound, such as increased tissue temperature, enhanced blood flow, reduced muscle spasms, and decreased pain receptor sensitivity, contribute to pain relief and functional recovery. Significant pain reduction was observed in the experimental groups compared to control groups, with consistent results across different studies. In conclusion, ultrasound therapy is a beneficial non-pharmacological intervention for managing non-specific LBP, offering significant improvements in pain relief and functional outcomes. Further research is recommended to optimize treatment protocols and confirm long-term benefits.